2009
DOI: 10.1080/13803390802134616
|View full text |Cite
|
Sign up to set email alerts
|

Attentional and executive functioning following mild traumatic brain injury in children using the Test for Attentional Performance (TAP) battery

Abstract: The interpretation of the data regarding cognitive outcome in children who have suffered from mild traumatic brain injury (MTBI) remains currently controversial. The aim of the present study is to explore attentional and executive functioning in 6-12-year-old children who experienced a MTBI. A total of 15 children with MTBI and 15 matched noninjured children participated in the study. Attentional tasks using the Test for Attentional Performance battery were administered one year after the injury. In comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 20 publications
2
47
0
Order By: Relevance
“…Other studies that directly compared attention functioning of mTBI patients with non-injured controls have generally reported null outcomes during both acute ( Jaffe et al, 1992) and chronic Babikian et al, 2011;Catroppa et al, 2011;Fay et al, 1994) injury phases (Babikian and Asarnow, 2009;Satz et al, 1997). However, subtle deficits (Catroppa et al, 2007), and adverse outcomes (Catale et al, 2009), have been occasionally reported in specific attention domains. Moreover, the wide heterogeneity in time post-injury in previous studies, coupled with variability in performance across a cohort in different developmental phases, may have hindered the ability to detect the effects of mTBI on cognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that directly compared attention functioning of mTBI patients with non-injured controls have generally reported null outcomes during both acute ( Jaffe et al, 1992) and chronic Babikian et al, 2011;Catroppa et al, 2011;Fay et al, 1994) injury phases (Babikian and Asarnow, 2009;Satz et al, 1997). However, subtle deficits (Catroppa et al, 2007), and adverse outcomes (Catale et al, 2009), have been occasionally reported in specific attention domains. Moreover, the wide heterogeneity in time post-injury in previous studies, coupled with variability in performance across a cohort in different developmental phases, may have hindered the ability to detect the effects of mTBI on cognition.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States alone, the rate of TBI-related emergency department visits was over 500 per 100,000 for children less than 17 years of age (Faul et al, 2010), and 75% of these injuries were classified as mild in nature (Centers for Disease Control and Prevention, 2003). While the majority of mild TBI (mTBI) patients fully recover within the first several months of injury (Babikian and Asarnow, 2009;Satz et al, 1997), a small subset of patients may experience persistent neurocognitive or psychosocial dysfunction for years (Anderson et al, 2001;Babikian et al, 2011;Catale et al, 2009;Fay et al, 2010;McKinlay et al, 2002McKinlay et al, ,2009McKinlay et al, ,2010Sterr et al, 2006), or even decades (Daneshvar et al, 2011;Hessen et al, 2007;Klonoff et al, 1993). Thus it is critical to identify neuroimaging and behavioral markers sensitive to mTBI to better understand recovery, and to prevent potentially long-term adverse outcomes from repeated mTBI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Catroppa and colleagues 16 found that 10 years after injury, children with mTBI were significantly impaired on a test of attentional gating or freedom from distractibility compared with typically developing (TD) children. Other studies have found deficits in tests of cognitive flexibility, 14 but few studies examined the trajectory of recovery after mTBI. 17 Therefore, consensus has not been reached with regard to the incidence and extent of EF impairment after mild TBI.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provided consistent evidence of few residual cognitive, behavioral, or academic deficits attributable to TBI beyond 3 months. Catale and colleagues, 14 however, suggested that results are mixed on studies of executive function (EF) after mTBI. For example, Roncadin and coworkers 15 found that children with mTBI performed within the normal range on verbal recognition memory, although it should be noted that this study examined patients with mild, moderate, and severe TBI, with no uninjured or extra-cranial injury comparison group.…”
Section: Introductionmentioning
confidence: 99%
“…There are well-documented significant ongoing impairments for children and adolescents following TBI, across physical, cognitive, educational, and behavioural domains (Catale, Marique, Closset, & Meulemans, 2009;Catroppa & Anderson, 2004;Catroppa, Anderson, Godfrey, & Rosenfeld, 2011;Catroppa et al, 2015;Crowe, Anderson, Barton, Babl, & Catroppa, 2014;Ganesalingam et al, 2011;Hawley, Ward, Magnay, & Mychalkiw, 2004;Max et al, 2005;Ryan et al, 2015). Such impairments contribute to increased risk of adverse outcomes in adolescence, such as school dropout, substance abuse, self-injurious behaviour, and entrance into the criminal justice system (Gunter, Chibnall, Antoniak, Philibert, & Black, 2013;McKinlay, Corrigan, Horwood, & Fergusson, 2014;Stoddard & Zimmerman, 2011).…”
Section: Introductionmentioning
confidence: 99%